An overview of drug‐induced sodium channel blockade and changes in cardiac conduction: Implications for drug safety - Khuram W. Chaudhary; Colleen E. Clancy; Pei‐Chi Yang; Jennifer B. Pierson; Alan L. Goldin; John E. Koerner; Todd A. Wisialowski; Jean‐Pierre Valentin; John P. Imredy; Armando Lagrutta; Simon Authier; Robert Kleiman; et al. (Clinical and Translational Science)
Abstract The human voltage‐gated sodium channel Nav1.5 (hNav1.5/SCN5A) plays a critical role in the initiation and propagation of action potentials in cardiac myocytes, and its modulation by various drugs has significant implications for cardiac safety. Drug‐dependent block of Nav1.5 current (INa) can lead to significant alterations in cardiac electrophysiology, potentially resulting in conduction slowing and an increased risk of proarrhythmic events. This review aims to provide a comprehensive overview of the mechanisms by which various pharmacological agents interact with Nav1.5, focusing on the molecular determinants of drug binding and the resultant electrophysiological effects. We discuss the structural features of Nav1.5 that influence drug affinity and specificity. Special attention is given to the concept of state‐dependent block, where drug binding is influenced by the conformational state of the channel, and its relevance to therapeutic efficacy and safety. The review also examines the clinical implications of INa block, highlighting case studies of drugs that have been associated with adverse cardiac events, and how the Vaughan‐Williams Classification system has been employed to qualify “unsafe” sodium channel block. Furthermore, we explore the methodologies currently used to assess INa block in nonclinical and clinical settings, with the hope of providing a weight of evidence approach including in silico modeling, in vitro electrophysiological assays and in vivo cardiac safety studies for mitigating proarrhythmic risk early in drug discovery. This review underscores the importance of understanding Nav1.5 pharmacology in the context of drug development and cardiac risk assessment.